ANALISIS HASIL VALIDITAS BAHAN AJAR FISIKA MATERI PERUBAHAN IKLIM BERBASIS WEB - Rahman Setiawan; Abdul Hakim; Zulkarnaen Zulkarnaen (Universitas Negeri Gorontalo, 2022)
This study aims to develop web-based physics teaching material. The ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model was used for the development of the teaching materials on climate change subject. This research focused on the validity aspect of the teaching material in the Development stage. The validity of teaching materials was based on two aspects: feasibility as physics material content and teaching media. The validity data were collected from experts and learning practitioners using validation instruments. The results showed that the developed web-based physics teaching material was categorized as good for physics material content with a validity level of 4.13. This teaching material was rated as very good as teaching media with a validity level of 4.55. Results of this study indicate that the developed web-based physics teaching material could be helpful for teaching topics related to climate change.